Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Sure! Let's find the derivative of the given function step-by-step.
### Given:
[tex]\[ f(x) = 2x \sin x \cos x \][/tex]
### Step 1: Differentiate [tex]\( f(x) \)[/tex] with respect to [tex]\( x \)[/tex].
To find the derivative [tex]\( f'(x) \)[/tex], we need to use the product rule and the chain rule. The product rule states that if you have a function [tex]\( g(x) = u(x)v(x) \)[/tex], then its derivative is given by:
[tex]\[ g'(x) = u'(x)v(x) + u(x)v'(x) \][/tex]
Let's set:
[tex]\[ u(x) = 2x \][/tex]
[tex]\[ v(x) = \sin x \cos x \][/tex]
First, we find the derivatives of [tex]\( u(x) \)[/tex] and [tex]\( v(x) \)[/tex]:
[tex]\[ u'(x) = 2 \][/tex]
To find [tex]\( v'(x) \)[/tex], we use the product rule again since [tex]\( v(x) = \sin x \cos x \)[/tex]:
Let,
[tex]\[ v_1(x) = \sin x \][/tex]
and,
[tex]\[ v_2(x) = \cos x \][/tex]
Then,
[tex]\[ v'(x) = v_1'(x) v_2(x) + v_1(x) v_2'(x) \][/tex]
[tex]\[ v_1'(x) = \cos x \][/tex]
[tex]\[ v_2'(x) = -\sin x \][/tex]
Now substitute:
[tex]\[ v'(x) = (\cos x) (\cos x) + (\sin x) (-\sin x) \][/tex]
[tex]\[ v'(x) = \cos^2 x - \sin^2 x \][/tex]
Now we can find [tex]\( f'(x) \)[/tex]:
[tex]\[ f'(x) = u'(x) v(x) + u(x) v'(x) \][/tex]
[tex]\[ f'(x) = 2(\sin x \cos x) + 2x(\cos^2 x - \sin^2 x) \][/tex]
Simplify it:
[tex]\[ f'(x) = 2 \sin x \cos x + 2 x (\cos^2 x - \sin^2 x) \][/tex]
You can also write it as:
[tex]\[ f'(x) = -2x \sin^2 x + 2x \cos^2 x + 2 \sin x \cos x \][/tex]
So the derivative of the function is:
[tex]\[ f'(x) = -2x\sin^2 x + 2x\cos^2 x + 2\sin x\cos x \][/tex]
---
### Step 2: Evaluate [tex]\( f'(x) \)[/tex] at [tex]\( x = 4 \)[/tex].
To find [tex]\( f'(4) \)[/tex], substitute [tex]\( x = 4 \)[/tex] into [tex]\( f'(x) \)[/tex]:
[tex]\[ f'(4) = -2(4)\sin^2(4) + 2(4)\cos^2(4) + 2\sin(4)\cos(4) \][/tex]
[tex]\[ f'(4) = -8\sin^2(4) + 8\cos^2(4) + 2\sin(4)\cos(4) \][/tex]
So the value of the derivative at [tex]\( x = 4 \)[/tex] is:
[tex]\[ f'(4) = -8\sin^2(4) + 2\sin(4)\cos(4) + 8\cos^2(4) \][/tex]
To summarize:
### Final Answers:
[tex]\[ f'(x) = -2x\sin^2 x + 2x\cos^2 x + 2\sin x\cos x \][/tex]
[tex]\[ f'(4) = -8\sin^2(4) + 2\sin(4)\cos(4) + 8\cos^2(4) \][/tex]
### Given:
[tex]\[ f(x) = 2x \sin x \cos x \][/tex]
### Step 1: Differentiate [tex]\( f(x) \)[/tex] with respect to [tex]\( x \)[/tex].
To find the derivative [tex]\( f'(x) \)[/tex], we need to use the product rule and the chain rule. The product rule states that if you have a function [tex]\( g(x) = u(x)v(x) \)[/tex], then its derivative is given by:
[tex]\[ g'(x) = u'(x)v(x) + u(x)v'(x) \][/tex]
Let's set:
[tex]\[ u(x) = 2x \][/tex]
[tex]\[ v(x) = \sin x \cos x \][/tex]
First, we find the derivatives of [tex]\( u(x) \)[/tex] and [tex]\( v(x) \)[/tex]:
[tex]\[ u'(x) = 2 \][/tex]
To find [tex]\( v'(x) \)[/tex], we use the product rule again since [tex]\( v(x) = \sin x \cos x \)[/tex]:
Let,
[tex]\[ v_1(x) = \sin x \][/tex]
and,
[tex]\[ v_2(x) = \cos x \][/tex]
Then,
[tex]\[ v'(x) = v_1'(x) v_2(x) + v_1(x) v_2'(x) \][/tex]
[tex]\[ v_1'(x) = \cos x \][/tex]
[tex]\[ v_2'(x) = -\sin x \][/tex]
Now substitute:
[tex]\[ v'(x) = (\cos x) (\cos x) + (\sin x) (-\sin x) \][/tex]
[tex]\[ v'(x) = \cos^2 x - \sin^2 x \][/tex]
Now we can find [tex]\( f'(x) \)[/tex]:
[tex]\[ f'(x) = u'(x) v(x) + u(x) v'(x) \][/tex]
[tex]\[ f'(x) = 2(\sin x \cos x) + 2x(\cos^2 x - \sin^2 x) \][/tex]
Simplify it:
[tex]\[ f'(x) = 2 \sin x \cos x + 2 x (\cos^2 x - \sin^2 x) \][/tex]
You can also write it as:
[tex]\[ f'(x) = -2x \sin^2 x + 2x \cos^2 x + 2 \sin x \cos x \][/tex]
So the derivative of the function is:
[tex]\[ f'(x) = -2x\sin^2 x + 2x\cos^2 x + 2\sin x\cos x \][/tex]
---
### Step 2: Evaluate [tex]\( f'(x) \)[/tex] at [tex]\( x = 4 \)[/tex].
To find [tex]\( f'(4) \)[/tex], substitute [tex]\( x = 4 \)[/tex] into [tex]\( f'(x) \)[/tex]:
[tex]\[ f'(4) = -2(4)\sin^2(4) + 2(4)\cos^2(4) + 2\sin(4)\cos(4) \][/tex]
[tex]\[ f'(4) = -8\sin^2(4) + 8\cos^2(4) + 2\sin(4)\cos(4) \][/tex]
So the value of the derivative at [tex]\( x = 4 \)[/tex] is:
[tex]\[ f'(4) = -8\sin^2(4) + 2\sin(4)\cos(4) + 8\cos^2(4) \][/tex]
To summarize:
### Final Answers:
[tex]\[ f'(x) = -2x\sin^2 x + 2x\cos^2 x + 2\sin x\cos x \][/tex]
[tex]\[ f'(4) = -8\sin^2(4) + 2\sin(4)\cos(4) + 8\cos^2(4) \][/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.